Introduction to controlled vocabularies : terminology for art, architecture, and other cultural works - Baca, Murtha (Getty Publications, 2013)
"This primer on the characteristics, scope, uses, and methods for building and maintaining controlled vocabularies for art and cultural materials explains how vocabularies should be integrated in cataloging systems; utilized for indexing and retrieval; and structured to group synonyms and arrange concepts into categories. The updated edition reflects recent developments in the field, including new national and international standards, current trends such as Linked Open Data, and revisions to the Getty vocabularies. The glossary and bibliography have also been updated." [contratapa]